EFFECT OF PLANT GROWTH PROMOTING MICROORGANISMS FROM RHIZOSPHERE OF PIPER NIGRUM L. - S. USHA; T. PADMAVATHI (International Journal of Pharma and Bio Sciences, 2013)
Six fungal isolates were selected from the rhizosphere of black pepper (Piper nigrum L.) plants and were tested in vitro for their plant growth promoting (PGP) abilities in the soil. The species of Aspergillus selected were tested for the siderophore production, indole acetic acid (IAA) production, catalase enzyme activity and biological control of pathogens through antagonism. The results indicated high degree of PGP ability in case of Aspergillus niger followed by A. flavus str1 with respect to all parameters. A.niger (12 U mL-1) and A. flavus str1 (10 U mL-1) showed higher siderophore production capabilities were able to produce indole acetic acid (IAA) in the range of 710µg mL-1 A. niger with a high catalase activity of 55.69 units mL-1 exhibited good biocontrol abilities against both Fusarium equiseticus (15.6 mm) and Mucor spp. (11.6 mm) suggesting that A. niger could be considered as a potential plant growth promoting fungi (PGPF).